Beban Kerja Perawat Dan Ketersediaan Sarana Dengan Penerapan Patient Safety - Wynda Permanasari Iksan; Silvia Dewi Mayasari Riu; Norman Alfiat Talibo (Lembaga Pengembangan Kinerja Dosen, 2025)
The success of implementing patient safety in the emergency department cannot be separated from various factors that influence it, one of which is the workload of medical staff.The availability of facilities also plays a significant role in the implementation of patient safety.The objective of this study is to determine the relationship between nurse workload and the availability of facilities with the implementation of patient safety in the Emergency Department of RSUD ODSK, North Sulawesi Province.The research uses a cross-sectional design.The sample in this study consisted of 30 respondents using the purposive sampling technique.Data collection on workload, facilities, and patient safety was conducted using a questionnaire and analyzed using the chi-square statistical test.The research results showed that the highest workload was the light workload category, with 21 respondents (70%).The most available facilities and infrastructure were found, with 21 respondents (70%).The most common implementation of patient safety was the implementation of patient safety in the good category, with 22 respondents (73.3%).The chi-square test results obtained p values of 0.003 and 0.032, where < α 0.05.Conclusion: There is a relationship between nurse workload and the availability of facilities with the implementation of patient safety in the Emergency Room of RSUD ODSK, North Sulawesi Province.